The Kingfisher facts and records book (London : Kingfisher, 2000)
This volume brings together nuggets of information relating to numerous topics, from the universe to atoms, from prehistoric times to the 21st century including space, nature, the human body, sport, science, money, art and culture.
Includes glossary and index
Primary
Keywords: World records